Temporal effects of final action on the performance of the Portuguese men's volleyball teams - Lima Ricardo; Silva Ana Filipa; Clemente Filipe Manuel (Sciendo, 2019)
Study aim: The purpose of this study was twofold: (i) to compare total attacks, points in the defense phase and attack efficiency between playing positions; and (ii) to identify the main predictors of overall volleyball teams' success related to points made during the game.